Québec contre Ottawa : axiomes et jeux de la communication - Lemieux, Vincent (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1978)
Present relations between the leadership teams of the Governments of Quebec and Ottawa may be interpreted by applying the axioms of communication pragmatics as formulated by Paul Watzlawick and his associates in drawing upon the ideas of Gregory Bateson. These axioms and other strategie considerations provide the basis for a game theory of politics that is itself applied to the debates between the leadership teams of Ottawa and those of Quebec. In the game theory of politics, primary concern is focused on tactical possibilities rather than on the usefulness of outcomes. Herein lies the relevancy of the idea of strategie move which has been introduced and developed by Schelling in order to render the theory of games more appropriate for the study of concrete situations.